Beyond Routine Exercise: Integrating Digital Problem-Posing Tools to Cultivate Creative Mathematical Fluency - Asmar Bani; Norma Angkotasan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2026)
Creative Mathematical Fluency (CMF), the ability to produce multiple, diverse, and original ideas with procedural accuracy, is crucial for 21st-century problem-solving. Still, routine drill and practice often fail to foster it. Studies indicate that problem-posing teaching can help students to generate divergent thoughts, but little is known about how digital problem-posing (DPP) tools influence CMF in real classrooms. The present study aimed to determine whether incorporating a cloud-based DPP curriculum in standard algebra-based lessons would improve middle-grade students' CMF scores compared to business-as-usual instruction, and to investigate the cognitive-affective processes associated with any such improvements. This six-week mixed-methods quasi-experimental research was conducted with 124 eighth-grade students at two similar Indonesian schools. Pre- and post-tests used the Creative Mathematical Fluency Test (CMFT) with Rasch-calibrated Fluency and Originality scales. Qualitative data identified richer structural diversity of posed problems, metacognitive reflection, and peer inspiration as driving factors. Students indicated increased enjoyment and eye percept creativity, despite some cognitive overload. Integrating DPP tasks meaningfully into algebra instruction can substantially raise CMF, suggesting that well-designed digital scaffolds can support learning